Transforming Balinese Folk Tales into E-books : Creative Solutions to Improve Reading Literacy and Speaking Skills - Sastra Dewi, Komang Ayu Tantri; Ardana, I Made; Jampel, I Nyoman (Jurnal Paedagogy, 2025)
The purpose of this research is to develop valid, practical, and effective Balinese Folk Tales e-book to improve reading literacy and speaking skills of elementary school students. This research method uses research and development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The subjects of this study were fifth grade students of Saraswati 4 Elementary School, Denpasar , Bali . Validity data were obtained through tests with reading literacy and speaking skills material experts, language experts, and learning media experts collected using a questionnaire instrument. Effectiveness test data were obtained through a quasi-experiment with a Non-equivalent control group design conducted on an experimental group of 32 students and a control group of 30 fifth grade elementary school students using a descriptive test instrument for reading literacy and a performance test for speaking skills. The data analysis used was one-way multivariate analysis of variance (Manova). The results of the study showed that the Balinese folklore E-book media for fifth grade elementary school students were stated to (1) Have characteristics that can refer to reading literacy and speaking skills indicators; (2) Very valid in terms of material, language, and learning media; (3) Very practical as studied from the perspective of students and practitioners; (4) Effective for improving students’ reading literacy and speaking skills.